Calcium Signaling in Pancreatic Immune Cells In situ. Issue 1 (13th October 2020) - Gryshchenko, Oleksiy; Gerasimenko, Julia V; Petersen, Ole H; Gerasimenko, Oleg V
Abstract: Immune cells were identified in intact live mouse pancreatic lobules and their Ca 2+ signals, evoked by various agents, characterized and compared with the simultaneously recorded Ca 2+ signals in neighboring acinar and stellate cells. Immunochemistry in the live lobules indicated that the pancreatic immune cells most likely are macrophages. In the normal pancreas the density of these cells is very low, but induction of acute pancreatitis (AP), by a combination of ethanol and fatty acids, markedly increased the number of the immune cells. The principal agent eliciting Ca 2+ signals in the pancreatic immune cells was ATP, but these cells also frequently produced Ca 2+ signals in response to acetylcholine and to high concentrations of bradykinin. Pharmacological studies, using specific purinergic agonists and antagonists, indicated that the ATP-elicited Ca 2+ signals were mediated by both P2Y1 and P2Y13 receptors. The pancreatic immune cells were not electrically excitable and the Ca 2+ signals generated by ATP were primarily due to release of Ca 2+ from internal stores followed by store-operated Ca 2+ entry through Ca 2+ release-activated Ca 2+ channels. The ATP-induced intracellular Ca 2+ liberation was dependent on both IP3 generation and IP3 receptors. We propose that the ATP-elicited Ca 2+ signal generation in the pancreatic immune cells is likely to play an important role in the severe inflammatory response to the primary injury of the acinar cells that occurs in AP. Graphical Abstract: